Peningkatan Kompetensi SMK dengan Keterampilan Computer Aided Design - Wajdi, Farid; Huddin, Muhammad Nurhaula; Maulana, Delly (Journal Pemberdayaan Masyarakat Indonesia, 2022)
Human capitals in the computer field are required in the Industrial Era 4.0. Vocational schools (SMK) are aimed to produce graduates who are ready-to-use to work in industries. However, SMK graduates are one of the major contributors to high unemployment in Indonesia. Teachers with skills in the field of computer technology are scarce. In addition, the facilities and infrastructure are limited in many SMK schools, especially in rural areas. This community service activity was carried out at SMK Muhammadiyah Tirtayasa. The school is located in the northern coastal rural area of Serang Regency. This community service activity provided assistance to Computer Aided Design (CAD) skills by targeting teachers and students. CAD skills can provide skills for vocational graduates who will have careers in industry. The result showed an increase in the skills of participants in the field of 2D/3D CAD drawing. The activity was very fruitful and can be further followed up by both expanding the partner schools or integrating school curriculum which adopts CAD skills with the aim of developing further the CAD knowledge.